Evaluation of the effects of topically applied simvastatin on titanium implant osseointegration - Dundar, Serkan; Bozoglan, Alihan (Elsevier B.V., 2020)
Objective: The aim of this study was to evaluate the effect of topical simvastatin on the osseointegration of machined-surface titanium implants. Material & methods: Sixteen female Sprague–Dawley rats were used in this study in a 4-wk experimental trial. The rats were divided into two groups: a test group (n = 8), in which local simvastatin was applied, and a control group (n = 8). In each of the 16 animals, a machined-surface titanium implant was surgically integrated into the tibial metaphysis. Prior to integration of the implants, 100 ?l of ethanol solution containing 5 mg of simvastatin was applied to the bone sockets. The implants were then immediately integrated into the bone sockets. No simvastatin treatment was applied in the control group. At the end of the 4-wk period, the rats were sacrificed, and the implants and surrounding bone tissue were removed. The bone–implant contact (BIC) and bone filling (BF) ratios of nondecalcified histological sections were then determined. The BIC ratio was defined as the ratio of the implant surface directly in contact with the bone to the total implant surface length. The BF ratio was determined by measuring the bone-filled area at a distance of 0.5 mm from implant. Results: There were no statistically significant differences in the BIC and BF ratios of the test group and control group in terms of implant osseointegration (p > 0.05). Conclusion: Within the limitations of this study, we conclude that topically applied simvastatin to implant surfaces does not affect osseointegration. © 2020
Keywords: Bone implant contact; Local application; Osseointegration; Rat tibia; Simvastatin